Domain-specific life satisfaction among older adults with and without children: The role of intergenerational contact. - Friederike Doerwald (Public Library of Science (PLoS), 2021)
Background Life satisfaction is associated with many important health outcomes among older adults and is an indicator of successful ageing. The present study aims to replicate earlier findings regarding relationships between satisfaction with various life domains and life satisfaction in older adults. The study furthermore explores how parental status is associated with satisfaction with different life domains and how two types of intergenerational contact (contact with own children; post-retirement work in childcare) relate to life satisfaction. Methods Participants were 1978 older adults, aged 65-75 year (51.7% female), who live in Bremen and took part in the OUTDOOR ACTIVE study. 82.6% of the participants had one or more children. All participants completed a questionnaire, which among others comprised items assessing life satisfaction as well as satisfaction with six different life domains (satisfaction with living situation, financial situation, leisure time, health, family, neighbors and friends). Results LS is significantly related to all of the investigated life domains, independent of sex and age. For the participants with children, life satisfaction had the highest association with satisfaction with family (β: 0.202; 95%CI: 0.170-0.235), followed by satisfaction with neighbors and friends (β: 0.151; 95%CI: 0.111-0.191), and health satisfaction (β: 0.148; 95%CI: 0.120-0.176). In comparison to that, participants without children had the highest association between life satisfaction and satisfaction with health (β: 0.193; 95%CI: 0.135-0.252), followed by satisfaction with family (β: 0.175; 95%CI: 0.114-0.236) and satisfaction with neighbors and friends (β: 0.154; 95%CI: 0.077-0.232). In participants with children, there was a non-significant negative association between life satisfaction and work in childcare (β: -0.031; 95%CI: -0.178-0.116), while life satisfaction was statistically significantly positively associated to work in childcare in participants without own children (β: 0.681; 95%CI: 0.075-1.288). Conclusions The results suggest that the domain-specific approach to life satisfaction can elucidate differences in the correlates of life satisfaction and well-being between older adults with and without children. They further suggest that the benefits of working with children for life satisfaction may be more pronounced in older adults without children than older adults with children.